(OC-6-35)-(2,2′-Bipyridine-κ2N,N′)dimethyl(3-sulfidopropionato-κ2S,O)platinum(IV) - Matthew S. McCready; Richard J. Puddephatt (Acta Crystallographica Section E, 2011)
The title complex, [Pt(CH3)2(SCH2CH2CO2)(C10H8N2)], is formed by the unusual oxidative addition of the disulfide, R2S2 (R = CH2CH2CO2H), to (2,2′-bipyridine)dimethylplatinum(II) with elimination of RSH. The product contains an unusual six-membered thiolate–carboxylate chelate ring. This slightly distorted octahedral complex exhibits cis angles ranging from 77.55 (11) to 97.30 (8)° due to the presence of the thiolate–carboxylate chelate ring and the constrained bipyridine group. The crystal packing appears to be controlled by a combination of π-stacking [centroid–centroid distance = 3.611 (2) Å] and C—H...O interactions.